2022
DOI: 10.3390/bs12110453
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COVID-19 Pandemic on the Frequent Use of E-Cigarettes and Its Association with Substance Use and Mental Health Symptoms

Abstract: Background: Although several studies examined the association between e-cigarettes, substance use, and mental health conditions, there is limited research on whether COVID-19-related stress and health outcomes, mental health symptoms, and substance use differ by the frequency of e-cigarette use during the COVID-19 pandemic. We assessed the association of past 30-day frequent use of e-cigarettes with alcohol, cannabis, anxiety/depression, and COVID-19 impact. Methods: We conducted a national online cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Specifically, the prevalence of dual use was higher in both immigrant and U.S.-born individuals who identified as non-binary/transgender, sexual minority, Black/African American, young adult, had less than high school education, experienced severe anxiety/depression symptoms, had higher loneliness scores, and used alcohol. These findings are consistent with the observations of other researchers, who found that individuals with lower and underserved socioeconomic and sociodemographic characteristics (e.g., young adults, people with less than high school education, sexual and gender minority persons, Black/African American individuals) and mental health disorder symptoms (e.g., anxiety/depression, stress) were more likely to engage in substance use, including e-cigarette and cannabis use, particularly their combinations ( Adzrago et al, 2022 ; Clendennen et al, 2021 , 2023 ; Conway et al, 2017 ; Duan et al, 2022 ; Kondracki et al, 2022 ; Lewis et al, 2022 ; Spears et al, 2019 , 2020 ; Thrul et al, 2020 ). However, none of the aforementioned studies examined subgroup differences in dual use of e-cigarettes and cannabis within immigrant and U.S.-born populations to identify immigration status-related disparities in dual use behavior for tailored substance use interventions aimed at reducing substance use and its health consequences, especially the increased risks of dual use of substances.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the prevalence of dual use was higher in both immigrant and U.S.-born individuals who identified as non-binary/transgender, sexual minority, Black/African American, young adult, had less than high school education, experienced severe anxiety/depression symptoms, had higher loneliness scores, and used alcohol. These findings are consistent with the observations of other researchers, who found that individuals with lower and underserved socioeconomic and sociodemographic characteristics (e.g., young adults, people with less than high school education, sexual and gender minority persons, Black/African American individuals) and mental health disorder symptoms (e.g., anxiety/depression, stress) were more likely to engage in substance use, including e-cigarette and cannabis use, particularly their combinations ( Adzrago et al, 2022 ; Clendennen et al, 2021 , 2023 ; Conway et al, 2017 ; Duan et al, 2022 ; Kondracki et al, 2022 ; Lewis et al, 2022 ; Spears et al, 2019 , 2020 ; Thrul et al, 2020 ). However, none of the aforementioned studies examined subgroup differences in dual use of e-cigarettes and cannabis within immigrant and U.S.-born populations to identify immigration status-related disparities in dual use behavior for tailored substance use interventions aimed at reducing substance use and its health consequences, especially the increased risks of dual use of substances.…”
Section: Discussionsupporting
confidence: 92%
“…Often closely associated with depression, electronic cigarette use is also positively correlated with both self-reported anxiety symptoms and generalized anxiety disorder (GAD) in humans (17,(52)(53)(54)(55)(56). While the directionality of this association is unclear, like depression, the relationship between anxiety and electronic cigarette use may also be bidirectional.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…This health crisis, marked by an intensified focus on personal health and safety, may have contributed to changes in attitudes and behaviors relating to e-cigarette use . Psychological stress and isolation that may have arisen from lockdown measures also may have prompted some individuals to increasingly depend on e-cigarettes and other tobacco products as a coping mechanism . In addition, the COVID-19 pandemic disrupted the conduct of surveys, especially those that relied on in-person data collection.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Psychological stress and isolation that may have arisen from lockdown measures also may have prompted some individuals to increasingly depend on e-cigarettes and other tobacco products as a coping mechanism. 14 , 15 In addition, the COVID-19 pandemic disrupted the conduct of surveys, especially those that relied on in-person data collection. As a result, surveys such as the NHIS transitioned from in-person to online interviews.…”
Section: Introductionmentioning
confidence: 99%